Figure 3 from: Cripps CL, Eberhardt U, Schütz N, Beker HJ, Evenson VS, Horak E (2019) The genus Hebeloma in the Rocky Mountain Alpine Zone. MycoKeys 46: 1-54. https://doi.org/10.3897/mycokeys.46.32823 - Cripps, Cathy L.; Eberhardt, Ursula; Schütz, Nicole; Beker, Henry J.; Evenson, Vera S.; Horak, Egon (Zenodo, 2019)
Figure 3 ML result of Hebelomasect.Naviculospora rooted in accordance with the results of Beker et al. (2016) with H.islandicum (internal outgroup). Branches supported by ≥ 80% bootstrap (1000 replicates) are indicated in red. Collections from the Rocky Mountains are indicated in bold, type sequences are indicated in blue.